Development of LINOSIAPPS as teaching materials to enhance information literacy of elementary school students based on Pantura local wisdom - Setiawaty, Rani; Nugraheni, Luthfa; Sufanti, Main; Purnomo, Eko; Cris Alonso T. Elle, Jude (BAHASTRA, 2026)
This study aims to develop LINOSIAPPS teaching materials to enhance information literacy of elementary school students based on Pantura local wisdom. The method used is Research and Development with the ADDIE model, including analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students of SD 1 Kesambi as the experiment and SD 2 Kesambi as the control, each with 22 students. The research instruments included expert validated questionnaires, teacher and student practicality questionnaires, and information literacy tests. The validation results showed that LINOSIAPPS was a very valid media (the average percentage of media expert validity was 90% and material expert 86.6%). The practicality test showed 96.5% student responses and 93.3% teacher responses, a very practical category. The effectiveness test using an independent t-test showed a significant difference (Sig. 0.000 <0.05) between the experimental and control groups, so LINOSIAPPS was effective in improving students' information literacy skills. The advantage of this media lies in the integration of e-module materials, interactive assessments, learning videos, and educational games that highlight the local wisdom of the Pantura area of Kudus, Pati, and Rembang. LINOSIAPPS supports contextual, engaging, and responsive Indonesian language learning to meet students' needs, while fostering local cultural awareness. Thus, LINOSIAPPS has proven valid, practical, and effective as an innovative teaching materials for strengthening information literacy in elementary school students.